Identifying requisite learning health system competencies: a scoping review. Issue 8 (23rd August 2022) - McDonald, Paige L; Phillips, Jessica; Harwood, Kenneth; Maring, Joyce; van der Wees, Philip J
Abstract : Objectives: Learning health systems (LHS) integrate knowledge and practice through cycles of continuous quality improvement and learning to increase healthcare quality. LHS have been conceptualised through multiple frameworks and models. Our aim is to identify and describe the requisite individual competencies (knowledge, skills and attitudes) and system competencies (capacities, characteristics and capabilities) described in existing literature in relation to operationalising LHS. Methods: A scoping review was conducted with descriptive and thematic analysis to identify and map competencies of LHS for individuals/patients, health system workers and systems. Articles until April 2020 were included based on a systematic literature search and selection process. Themes were developed using a consensus process until agreement was reached among team members. Results: Eighty-nine articles were included with most studies conducted in the USA (68 articles). The largest number of publications represented competencies at the system level, followed by health system worker competencies. Themes identified at the individual/patient level were knowledge and skills to understand and share information with an established system and the ability to interact with the technology used to collect data. Themes at the health system worker level were skills in evidence-based practice, leadership and teamwork skills, analytical and technological skills required to use a 'digital ecosystem', data-science knowledge and skill and self-reflective capacity. Researchers embedded within LHS require a specific set of competencies. Themes identified at the system level were data, infrastructure and standardisation; integration of data and workflow; and culture and climate supporting ongoing learning. Conclusion: The identified individual stakeholder competencies within LHS and the system capabilities of LHS provide a solid base for the further development and evaluation of LHS. International collaboration for stimulating LHS will assist in further establishing the knowledge base for LHS.